(untitled) (Revista de História da UEG (REVHIST), 2021)
The present paper seeks to analyze the defense strategy of the colonial populating in the Capitania of Pernambuco through the establishment of Indian settlements in the areas where there was a higher incidence of attacks by palmaristas in the seventeenth century. Besides the various interests of colonial agents connected to the work of the natives in the villages, in times of war, the colonial villages also took on the function of military encampment, sheltering soldiers from the expeditions and serving as walls that prevented the advance of enemy forces. Thus, the present study also seeks to identify the villages that served this purpose. We use as sources administrative correspondence found in the main documental collections related to the colonial period of Brazil, as well as reports from chroniclers and colonial maps, analyzed and problematized through the reflections made by colonial Indian historiography. Keywords: Indian settlements. Military encampment. Palmaristas.